Relationship between Chlamydia trachomatis infection and Repeated Abortion in Iraqi pregnant Women - Hammadi, Amer A.; Wahed, Hameedah H. A.; Adnan, Hadeel; Abbas, Lamia.F.; Sadiq, Alaa; Maki, Shukira A.; Amer, Batool; Khaled, Sahar (Scientific Journal of Medical Research, 2022)
Background: Chlamydia trachomatis (C. trachomatis); was even a little reason for the frequent abortion in women. Objective: The study aimed to know the relationship between C. trachomatis infection and women who suffer from repeated abortion. Methods: A total of 104 women, ages ranging from (15-50) years, were enrolled in the current studies, and each patient and control blood samples were collected. And estimation of IgG and IgM levels against C. trachomatis in sera of patients was done using ELISA method. Results: Based on the ELISA screening assay, the level of circulating C. trachomatis -specific IgG and IgM antibodies between the patients is 4.8%. of total infections in three Iraqi cities, there is a relation between age and repeated abortion. In most abortion cases, more than 46 years old in 15.3%, and the abortion in pregnant women in the first period of gestation with three positive and the result shows there is no relation between abortion and area of life. Conclusion: C. trachomatis infection is an important causative agent of miscarriages in women. C. trachomatis infection diagnostic procedures should be considered in screening tests during pregnancy.